Risk attitude in couples - Philomena M. Bacon; Anna Conte; Peter G. Moffatt (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2012)
The determinants of risk attitude in couples are explored using data from the German Socio-Economic Panel over the period 2004 to 2009. The focus of the analysis is the repeated responses to the survey question about general willingness to take risk. Responses to this question are provided on a 0-10 Likert scale. We focus on couples in the data set, and we apply the bivariate panel ordered probit model to the analysis of the simultaneous determination of the male's and the female's risk attitude. A number of individual characteristics, including age, height, education and household income, are found to have strong effects on risk attitude, in some cases differing markedly between the male and the female. Both the individual-specific effects and the observation-specific error terms are assumed to have non-zero correlations between the two equations. These correlations are estimated to be +0.27 and +0.28 respectively. We consider the former to be a key parameter, since its positive sign may be interpreted as a form of homophily: individuals tend to form partnerships with others having a similar risk attitude.
Keywords: C33; D81; 330; Multiple Equation Models; Panel Data; Risk Attitude; Risikopräferenz; Geschlecht; Ehe; Deutschland